The effect of indoor environment quality on productivity in oil painting art studios - Alherani, Rawan Majed; Alnusairat, Saba (Frontiers in Built Environment, 2026)
Oil painting studios require optimal indoor environments to improve artist health and productivity. This experimental study employs a mixed-methods approach to investigate the influence of indoor environmental quality (IEQ) on the productivity of two oil painting art studios, which were chosen for their similar environmental conditions and layouts. However, both studios are different in terms of IEQ, including air quality, lighting, thermal conditions, and acoustics, allowing for a comparative analysis. The data collection includes field measurements, questionnaires, observations, and productivity assessments, which are analyzed using descriptive statistics and environmental assessments. The research is done through three phases: pre-painting assessments, observation during the painting stage, and post-painting evaluations. With Studio One exhibiting enhanced outcomes compared to Studio Two, the findings suggest that studios with more favorable indoor environmental conditions—particularly regarding ventilation, thermal stability, and lighting—are associated with improved comfort and shorter task completion times. However, the comparative nature of the study limits causal attribution. In addition to highlighting the broader implications of IEQ factors in the studio, this experimental study emphasizes the importance of enhancing indoor conditions in art studios to most likely support artist productivity and health.